Linking biodiversity into national economic accounting. Issue 116 (February 2021) - King, Steven; Vardon, Michael; Grantham, Hedley S.; Eigenraam, Mark; Ferrier, Simon; Juhn, Daniel; Larsen, Trond; Brown, Claire; Turner, Kerry
Highlights: Framework that links biodiversity indicators to national economic accounts. Case studies presenting the state of the art in accounting for biodiversity. Informing holistic land use and economic planning for sustainable development. Abstract: Biodiversity underpins the supply of ecosystem services essential for well-being and economic development, yet biodiversity loss continues at a substantial rate. Linking biodiversity indicators with national economic accounts provides a means of mainstreaming biodiversity into economic planning and monitoring processes. Here we examine the various strategies for biodiversity indicators to be linked into national economic accounts, specifically the System of Environmental-Economic Accounts Experimental Ecosystem Accounting (SEEA EEA) framework. We present what has been achieved in practice, using various case studies from across the world. These case studies demonstrate the potential of economic accounting as an integrating, mainstreaming framework that explicitly considers biodiversity. With the right indicators for the different components of biodiversity and scales of biological organisation, this can directly support more holistic economic planning approaches. This will be a significant step forward from relying on the traditional indicators of national economic accounts to guide national planning. It is also essential if society's objectives for biodiversity and sustainable development are to be met.